Effect of cell surfaces on the stability of chiral smectic- C phases - VIJ, JAGDISH; MANNA, UTTAM; SONG, JANG-KUN (My University, 2008)
The effect of surfaces on the stability of smectic-C* (SmC*) variant phases is investigated. The results obtained using dielectric spectroscopy by varying the cell thickness show that the temperature ranges of SmCalpha*, SmCA*(1/2), and SmCA*(1/3) phases decrease with decreasing cell thickness, and the SmCA*(1/3) phase is more stable than the SmCA*(1/2) phase. The relative stability of any phase is found to be due to its large polar anchoring strength and low free energy compared to other phases in a cell. Experimental results are found to agree with the theory.
PUBLISHED
Keywords: Electronic & Electrical Engineering